The power of many values for success in business and in life - Whitman, Meg; Hamilton, Joan O'C (Crown Publishers, 2010)
Is it possible to run a multibillion-dollar corporation on the power of trust? Must you set aside your authentic self as you climb the corporate ladder? Is there another role for technology beyond saving costs and creating efficiencies? In The Power of Many, Meg Whitman, former president and CEO of eBay, speaks to these questions and more, identifying ten core values that steered her—and can steer any leader—to success without ethical compromise.